2015
DOI: 10.12707/riv14077
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ perception of nurses’ breastfeeding promotion practices

Abstract: Resumenpp.65-73 Resumo Revista de Enfermagem Referência A R T I G O D E I N V E S T I G A Ç Ã O ( O R I G I N A L ) Perceção das mães sobre as práticas dos enfermeiros na promoção do aleitamento maternoMothers' perception of nurses' breastfeeding promotion practices La percepción de las madres sobre las prácticas de los enfermeros en la promoción de la lactancia maternaRaquel José Silva Castro*; Ernestina Maria Batoca Silva**; Daniel Marques Silva*** Enquadramento: Amamentar é um ato cujo sucesso depende de fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A study aimed at identifying mothers' perceptions of nurses' practices in promoting breastfeeding revealed that most mothers (41.5%) were advised to breastfeed exclusively up to 24 months or more and 31.7% up to six months. Mothers (86.2%) reported that most of them were informed about the benefits of exclusive breastfeeding and 64.4% received information about the legislation regarding labor rights during the exclusive breastfeeding period (28) .…”
Section: Discussionmentioning
confidence: 99%
“…A study aimed at identifying mothers' perceptions of nurses' practices in promoting breastfeeding revealed that most mothers (41.5%) were advised to breastfeed exclusively up to 24 months or more and 31.7% up to six months. Mothers (86.2%) reported that most of them were informed about the benefits of exclusive breastfeeding and 64.4% received information about the legislation regarding labor rights during the exclusive breastfeeding period (28) .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, most mothers in rural and urban Cameroon ranked Doctors and nurses as the most important source of advice with the greatest impact on their BF decision (Lem, 2015). Also, previous research by Castro et al (2015) and Taveras et al (2004) also showed that mothers often identify BF promotion interventions given by healthcare professionals as the single most important intervention that could have been offered to help them breastfeed. More so, Nguyen et al (2018) investigated the factors that influenced the mothers' BF decision in Da Nang, Viet Nam, and found that health professionals were the most influential, followed by close family members.…”
Section: Effects Of Sources Of Bf Information On Maternal Decisionmentioning
confidence: 96%
“…Professional support was a positive determining factor for the decision, establishment, and maintenance of breastfeeding 14,15 . This professional support is represented in the study by nurses, and it is evident through the analysis of the narratives that they accompany the woman throughout the pregnancy-puerperal cycle 16,17 .…”
Section: the Professional Supportmentioning
confidence: 99%